Does the gelation temperature or the sulfuric acid concentration influence the dosimetric properties of radiochromic PVA-GTA Xylenol Orange Fricke gels?. (July 2019) - Gallo, Salvatore; Gambarini, Grazia; Veronese, Ivan; Argentiere, Simona; Gargano, Marco; Ianni, Luca; Lenardi, Cristina; Ludwig, Nicola; Pignoli, Emanuele; d'Errico, Francesco
Abstract: Purpose of this study is to test if possible effects of gelation temperature and pH on the cross-linking process between poly(vinyl alcohol) (PVA) and glutaraldehyde (GTA), have consequences on the dosimetric properties of PVA-GTA Xylenol Orange Fricke gel dosimeters. Therefore, dose-response curves and Fe 3+ diffusion rate of PVA-GTA Fricke gel dosimeters prepared using different sulfuric acid concentrations and different gelation temperature were investigated by optical absorbance measurements. The results demonstrated that the sulfuric acid concentration determines both the dose sensitivity of the PVA-GTA Xylenol Orange Fricke gel dosimeters and the interval of linearity of the dose-response curve. Although the effects of gelation temperature and sulfuric acid concentration on the PVA-GTA cross-linking process may occur, no significant consequences on diffusion properties of PVA polymer network were observed. Indeed, Fe 3+ diffusion rates in all investigated samples were very similar, and less than half of those achievable in Fricke gel dosimeters prepared with natural gel matrices like gelatin and agarose. Highlights: Gelation temperature and sulfuric acid concentration do not affect the diffusion rate of Fe 3+ in PVA-GTA XO Fricke gels. The dose response curve of the PVA-GTA XO Fricke gels are independent of the gelation temperature. Sulfuric acid concentration determines the sensitivity and the interval of linearity of the dose response in PVA-GTA XO Fricke gels.